2011
DOI: 10.1037/a0025974
|View full text |Cite
|
Sign up to set email alerts
|

Clinics-in-common: Creating uncommon professionals.

Abstract: i at Ma noa Most professional educational programs develop specialized experts who view problems from the perspectives of their own disciplines. Yet, our most pressing social problems are rarely limited to a single disciplinary approach. Instead of providing future professionals with the tools necessary for solving problems that cross disciplines, many professional training programs inadvertently stifle multidisciplinary communication and collaboration by isolating students from students in other disciplines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…However,, other disciplines, such as education and public health, have shown utility in collaborating with community partners to enhance outcomes for the community as well as individuals (Barrera, 2015;Parker et al, 2017). In Hawaii, Kimura et al (2011) studied the importance of working across disciplines and developing partnerships as a way to expand training programs for students in education, law, nursing and social work. They found that using a collaborative and multi-disciplinary approach was beneficial to the students' professional development.…”
mentioning
confidence: 99%
“…However,, other disciplines, such as education and public health, have shown utility in collaborating with community partners to enhance outcomes for the community as well as individuals (Barrera, 2015;Parker et al, 2017). In Hawaii, Kimura et al (2011) studied the importance of working across disciplines and developing partnerships as a way to expand training programs for students in education, law, nursing and social work. They found that using a collaborative and multi-disciplinary approach was beneficial to the students' professional development.…”
mentioning
confidence: 99%